TOWARDS THE CREATION OF A DEVELOPMENTAL WELFARE STATE IN ZIMBABWE: AN INSIDE PERSPECTIVE ON THE DEPARTMENT OF SOCIAL DEVELOPMENT - Kurevakwesu, Wilberforce; Dzoma, Fanuel; Mundau, Mulwayini; Magocha, John Chiwanza; Chizasa, Simbarashe; Takangovada, Mary (Social Work, 2022)
In June 2020 the government of Zimbabwe issued a statement of intent towards embracing a developmental social welfare approach by changing the name of the Department of Social Welfare to the Department of Social Development. This has been a long-awaited move in the indigenisation of Zimbabwe’s social welfare services. However, despite such a strong and progressive commitment by the government, there is no clear framework on how the Department of Social Development plans to implement developmental social welfare services in Zimbabwe. It is this concern that we address as we take an ‘inside perspective’ on the work of the Department of Social Development towards explicating current programmes and services, and examine available information on how the Department intends to reorientate Zimbabwe’s social welfare system. We then offer recommendations that can be used by the DSD towards the creation of a developmental welfare state in Zimbabwe. Keywords: developmental social welfare, Department of Social Development indigenisation, social welfare, welfare state, social welfare services, Zimbabwe